Pengaruh Pemberian Jamu Sehat Tanaman (JST) Raja Hara PS 200 dan Vermikompos Terhadap Pertumbuhan Bawang Merah Samosir (Allium ascalonicum L.) - Ritonga, Muhammad Alvi; Zulfida, Ida; Dewi, Dora Silvia (UNIVERSITAS LABUHANBATU, 2024)
The shallot plant (Allium ascalonicum L.) from the liliceae family originates from Central Asia, is one of the main horticultural products which is often used as a food flavoring. Quality shallot production is obtained by carrying out appropriate cultivation steps, one of which is meeting the plant's nutrient needs. Efforts that can be made to increase the production of Samosir Shallots (Allium ascalonicum L.) are by organic cultivation using Raja Hara PS 200 Plant Healthy Herbal Medicine (JST) and Vermicompost. The use of Raja Hara PS 200 Plant Healthy Herbal Medicine (JST) and Vermicompost is carried out to reduce the use of chemical fertilizers so that it can increase the nutrients in the soil. This research was conducted to determine the effect of giving Raja Hara PS 200 Plant Healthy Herbal Medicine (JST) and Vermicompost on the vegetative growth of Samosir Shallots (Allium ascalonicum L.). This research was conducted in July-September 2024. The method materials used were Samosir Shallot tubers, Plant Healthy Herbal Medicine (JST) Raja Hara PS 200 and Vermicompost. The method used in this research was a Randomized Group Design (RAK) which consisted of 1 treatment and 3 replications. Test analysis uses further analysis of variance with Duncan's Multiple Range Test (DMRT) 5%. The administration of Plant Healthy Herbal Medicine (JST) Raja Hara PS 200 and Vermicompost did not show any real differences in all growth variables, however, there was a tendency that the longer the time after administration of Plant Healthy Herbal Medicine (JST) Raja Hara PS 200 and Vermicompost, the greater the growth yield of Samosir Shallots. (Allium ascalonicum L.)Keywords: Samosir Shallots (Allium ascalonicum L.), Plant Healthy Herbal Medicine (JST) Raja Hara PS 200, Vermicompost